Situs-Situs Megalitik di Desa Padangratu, Kecamatan Buay Pematangbiru, Kabupaten OKU Selatan : Tinjauan Bentuk Lahan dan Material - Siregar, Sondang M; Irawan, Dio (Badan Riset dan Inovasi Nasional, 2022)
The Padangratu area have landforms formed as a result of natural and human activities. Within the Padangratu area, archaeological remains made from various materials are scattered. The problem is the shape of the land and materials in the Padangratu area. The method used is a qualitative method with exploratory and descriptive research types. The results of the research show that in the Padangratu area there are megalithic buildings and artifacts spread across the Jurun, Langkat, Putor, Tanjung and Tanjung Mandak sites. These sites are spread across the plateau at an altitude of 0 to 1000 meters above sea level. Putor, Langkat and Tanjung hamlets are at an altitude of 500 masl to 750 masl, while Jurun Hamlet is at an altitude of 750 masl to 1000 masl. This location is on a very gentle slope (3%-7%) to quite steep (14%-20%), especially in an area where the erosion rate is very low. In the Padangratu area, 47 flat stones, 3 dolmens, 1 stone bracelet, 1 stone mortar were found which were generally made of tuff. Apart from that, stone mortars made of pumice, square axes made of chalcedony, obsidian fragments and clay pottery containers were found. These materials are volcanic materials obtained from the area around Lake Ranau. Apart from that, the Padangratu area is located in the stratifigraphy of the Ranau rock formation which contains tufa, pumice and clay materials.